Kemajuan Teknologi Rekayasa Genetika Ditinjau dari Filsafat Evolusi Darwin - Geterudis Kerans (Undiksha, 2022)
Evolution occurs because of the process of changing species within a certain period of time with the aim of being able to adapt to their environment and these changes will be passed on to the next generation or to their descendants. The theory of evolution in the Biological Sciences came to light with the publication of Charles Darwin's book (On the Origin of Species by Means of Natural Selection) in 1859, which presented cases of evolution and was able to relate previously confusing collections of facts. In the 1930s scientists combined Darwin's natural selection with Mendelian's theory of heredity and formed the modern evolutionary synthesis